2016
DOI: 10.3906/biy-1506-66
|View full text |Cite
|
Sign up to set email alerts
|

Production of 2,3-butanediol by Enterobacter cloacae from corncob-derived xylose

Abstract: During the process of industrial production of biofuels and biochemicals from lignocellulosic biomass, large amounts of waste byproducts rich in xylose are generated, resulting in excessive wastage of natural resources and environmental pollution. In this work, xylose solution from corncob hydrolysate was utilized to produce 2,3-butanediol (2,3-BD), using the strain Enterobacter cloacae CICC 10011 to improve the utilization rate of hemicellulose and reduce environmental pollution. 2,3-BD fermentation condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…The highest BDO titer of 81.4 g/L using xylose solution from corncob hydrolysate and corn liquor (20 g/L) has been reported by E. cloacae with a conversion yield of 0.39 g/g and a productivity of 0.72 g/L·h . Unlike our work where forced pH fluctuation was employed, the pH was controlled in the case of other bacterial strains.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The highest BDO titer of 81.4 g/L using xylose solution from corncob hydrolysate and corn liquor (20 g/L) has been reported by E. cloacae with a conversion yield of 0.39 g/g and a productivity of 0.72 g/L·h . Unlike our work where forced pH fluctuation was employed, the pH was controlled in the case of other bacterial strains.…”
Section: Discussionmentioning
confidence: 81%
“…Summary of Microbial BDO Production from Pure/Crude Xylose /g and a productivity of 0.72 g/L•h 31. Unlike our work where forced pH fluctuation was employed, the pH was controlled in the case of other bacterial strains.…”
mentioning
confidence: 97%
“…2,3-Butanediol (2,3-BDO) is an important platform compound with applications in aerospace, food, pharmaceuticals, chemicals, and fuels (Priya and Lal 2019). Along with the increasing problems of crude oil scarcity, rising fossil fuel prices, and the everincreasing-environmental pollution, the synthesis of 2,3-BDO by biological methods has regained widespread attention (Zhang et al 2016). The main substrates used for the biosynthesis of 2,3-BDO are glucose and glycerol.…”
Section: Introductionmentioning
confidence: 99%
“…The 2,3-BD industry has been more popular as of recent because of the increased research on 2,3-BD conversion from renewable sugars and agricultural wastes. Previous studies have shown that high titers of 78.9 g/L 2,3-BD can be produced from Klebsiella pneumoniae and 81.4 g/L from Enterobacter cloacae . However, these organisms are classified as risk 2 and pose certain health concerns .…”
Section: Introductionmentioning
confidence: 99%
“…8−11 Previous studies have shown that high titers of 78.9 g/L 2,3-BD can be produced from Klebsiella pneumoniae 12 and 81.4 g/L from Enterobacter cloacae. 13 However, these organisms are classified as risk 2 and pose certain health concerns. 14 Organisms generally regarded as safe (GRAS) pose less risk and include several common Bacillus species.…”
Section: ■ Introductionmentioning
confidence: 99%